O governo da língua na cabanagem: (des)encontros coloniais na Amazônia - LAVAREDA, Welton Diego Carmim (Universidade Federal do Pará, 2023)
The research that resulted in the current doctoral thesis analyzes in general, how the different governmentality strategies defined by the colonial device, during the period of Cabanagem, favored the establishment of a European linguistic heritage in the Amazon, inserted in a series of conflicts, predominantly, linguistic. Taking as a starting point the archivist series cataloged in the Public Archives of Pará, in the Public Archives of the Municipalities of Cametá-PA and Vigia de Nazaré-PA, in the Foreing Office (London) and in the publication “Political Riots or history of the main events politicians in the Province of Pará from 1821 to 1835 ”(1970), this research proposes, in a specific way, to map the historical movements and the linguistic practices experienced at the time of the colonization (which served as base for the analyzes). Also in a specific way, we seek to identify which discursive tensions were legitimized, by the colonial device, for the maintenance of a government of the language that favored the European linguistic management in the Cabana Province (1835-1840). The theoretical and methodological framework were built under the basis of interdisciplinary dialogues that could refer to historical experience, adopting as main analytical basis the archeogenealogical perspective of Michel Foucault's discursive studies (1964; 2009; 2008, 2010a; 2010b; 2010c; 2011; 2016a; 2016b ). In order to understand the process of lusitanization and the historical emergencies of linguistic policies related to the Colonial Period, we turn to Rosa Virgínia Mattos e Silva (2004), Cristine Severo (2013; 2014; 2016) & Sinfree Makoni (2015) and Bessa Freire (2011). When we mobilizing the dimension of linguistic necropolitics and the concept of language in recent modernity, we follow the studies and conceptual operationalization that has been developed by GEDAI-CNPq (LAVAREDA & NEVES, 2018; 2019; 2020; OLIVEIRA, 2018; NEVES- CORRÊA, 2018; LISBÔA, 2019). By using as a reference the definition of coloniality of power guided by decolonial studies, driven by Aníbal Quijano (1999; 2005), and adopting the constitution of the language through the bias of modernity and coloniality as mutually constitutive projects (MIGNOLO, 2020; MARTÍN-BARBERO, 2009 ; 2014; WALSH, 2019), we moved the discussions about the colonial device proposed by Ivânia Neves (2009; 2015; 2020), in order to think about the technologies of power that are still active in the production processes of the subjectivities of Amazonian societies and of the discourses that circulate over them. The research on the cabano movement observed by Magda Ricci (2001; 2016), the studies on Afro-Brazilian populations in the social struggles and ethnic composition of Pará and on the Cabanagem, carried out by Vicente Salles (1992; 2005; 2015), also compose the global theoretical architecture of the proposed debates. Finally, it is ratified that the “invention” of a Portuguese-speaking government in the Cabano scenario intensified the transposition of varied discursive genres to the conditions of emergence of colonized peoples in the Brazilian Amazon and, in the same direction, potentiated the emergence of metacategories that were taken as discourses of truth until the history of the present.